GIS Web-based Platform for Experimentation Using Environmental Geosensors - Ribeiro, Alexandra; Sousa, Vitor; Cardoso, Alberto (International Journal of Online and Biomedical Engineering (iJOE), 2016)
This work describes a GIS web-based open source platform for wireless in situ geosensor data visualization and distributed geoprocessing. Emphasis is put on: i) visualization of sensor measurements and sensor location on a map; ii) geoprocessing of these data; iii) and, visualization of geoprocessing results on a map. The platform combines the Open Geospatial Consortium (OGC) Sensor Web Enablement (SWE) standards, in particular the Sensor Observation Service (SOS), and the OGC Web Processing Service (WPS). Several results are presented using different methods of spatial interpolation of air temperature measurements as geoprocessing tasks.